Educational and Career Development Outcomes Among Undergraduate Summer Research Interns: A Pipeline for Pathology, Laboratory Medicine, and Biomedical Science. (12th December 2019) - Howell, Lydia Pleotis; Wahl, Sharon; Ryan, John; Gandour-Edwards, Regina; Green, Ralph
Nurturing undergraduate students' interest in careers in science, technology, engineering, and medicine is important to developing the future health-care workforce. Summer research internships provide experiential learning that is important to sustaining students' interest in science, technology, engineering, and medicine careers and inspiring higher educational goals. The Edmondson Summer Research Internship is a mentored program for undergraduate students in University of California Davis Health's Department of Pathology and Laboratory Medicine. To evaluate intern satisfaction, perceptions on the program's influence on their career development, and higher educational outcomes, 102 former interns from a 15-year period were invited to participate in an online survey. Responses were received by 58 (57%) of 102 respondents. Not all respondents answered every question. Overall satisfaction was very high/high in 55 (95%) of 58. Ninety-three percent (54/58) strongly agreed/agreed that the internship was an important part of their career development. Almost all who applied to career/professional opportunities strongly agree/agreed that they perceived the internship to be advantageous (96%, 46/48). Forty-four percent (25/57) received additional education after completing their undergraduate degree, with 25% (14/57) receiving a doctoral degree. Few reported prior experience with a clinical laboratory (8/48, 17%), pathologist (10/48, 21%), or clinical laboratory scientist (12/48, 25%). Based on their internship experience, 55% (32/58) strongly agree/agreed that they positively considered pathology or laboratory medicine as a career choice. The Edmondson Summer Research Internship is seen as important to higher educational goals and career development, increases exposure to pathology and laboratory medicine, and demonstrates the value of hosting a mentored research program for undergraduates.